(untitled) (Quest Journal of Management and Social Sciences, 2019)
Background: Effective banking communication strengthens the relationship between customer, suppliers, stakeholders, manager, client, employees and board of directors. Banker’s experience on banking communication enhances banking system, employee’s behavior and core banking services facilities management. Banking communication improves organizational effectiveness through training, knowledge management, risk management, internal control system and data security management. In modern era, communication channel is transformed into electronic channel promoting e-banking which includes internet banking, mobile banking and e-payment system. Moreover, clerical work shifted into electronic form, which cut costs and satisfy customer. Objectives: This paper explores how banker’s experience effects on banking communication in commercial banks, which enhances their understanding level and determines effective communication in workplace. Methods: Extensive desk reviews followed by related literature werecarried out to gain better insight regarding the field of study. Findings: With the passage of time, computers and technologies have changed the traditional method of communication system. Banks are now using windows, world processing system, excel, computer operating system, DOS, database management system, data planning and database design, data security, internet, intranet, extranet service and email system which increase working performance. Conclusions: Bank managers need to understand importance of communication skills in order to increase effectiveness of internal communication between manager and employees. Implications: Commercial banks of Nepal requireto update in their communication practices and strategies in order to build proper channel which would help in communication between employees and management.